Mengukur Behavioral Intention Wisatawan Di Era New Normal Pandemi Covid-19 Di Kota Padang Berbasis Experience Economy Dan Emotion - Yofina Mulyati; Amelia Ardiyani; Yulisran B. Putra (Jurnal Penelitian Dan Pengkajian Ilmiah Sosial Budaya, 2022)
This study aims to measure the behavioral intention of tourists in the new normal era of the COVID-19 pandemic in Padang City based on the experience economy and emotion. The population in this study were all tourists who came to visit tourist destinations in the city of Padang in the new normal era of the COVID-19 pandemic, the number of which was not known with certainty, with a total sample of 138 tourists. The sampling technique used purposive sampling method. Analysis of the data used is Partial Least Square (PLS). Based on the results of the study, the results are summarized as follows: (1) The experience economy has a significant positive effect on tourist emotions in the new normal era of the COVID-19 pandemic in Padang City, (2) the experience economy has a significant positive effect on the behavioral intention of tourists in the new normal era. the COVID-19 pandemic in the city of Padang, (3) emotion has a significant positive effect on the behavioral intention of tourists in the new normal era of the covid-19 pandemic in the city of Padang and (4) the experience economy has a significant positive effect on the behavioral intention of tourists in the new normal era of the covid-19 pandemic. 19 in Padang City through emotion.